Developing a Scale for Attentional Control and its Relationship to Competitive Anxiety in Sports Among Players of some First Division Football Clubs for the 2024-2025 Sports Season - Abed Sarwal Ghali (Psikologia : Jurnal Psikologi, 2027)
General Background: Competitive football requires sustained concentration and attentional regulation because players must respond to rapidly changing situations while managing competitive pressure and anxiety. Specific Background: First-division football players encounter concentration difficulties, anxiety, distraction, and decision-making challenges during matches, creating a need to examine attentional control and competitive anxiety systematically. Knowledge Gap: The study addresses the need for a specific attentional control scale and an assessment of its relationship with competitive anxiety among first-division football players. Aims: This study develops an attentional control scale, determines competitive anxiety levels, and examines the relationship between attentional control and competitive anxiety. Results: The study used a descriptive survey design involving 128 players, including 18 players in the exploratory study and 110 in the main study. The attentional control instrument comprised 30 items across five dimensions: task focus, attentional control, resistance to distractions, selective attention, and maintaining focus and attention. Expert agreement ranged from 88.88% to 100%, while Cronbach’s alpha coefficients were 0.836 for attentional control and 0.824 for sports competition anxiety. The reported correlation coefficients between competitive anxiety and the five attentional-control dimensions were 0.035, 0.038, 0.074, 0.070, and 0.029, respectively. Novelty: The study develops and applies two structured psychological scales specifically for first-division football players. Implications: The findings support continued psychological guidance and training focused on concentration, attentional control, distraction resistance, selective attention, and sustained attention during football preparation and competition. Highlights: The measurement instrument comprised 30 attentional-control items across five dimensions. Expert agreement for the proposed dimensions ranged from 88.88% to 100%. Reliability coefficients reached 0.836 and 0.824 for the two psychological scales. Keywords: Attentional control, Competitive anxiety, Players, Focus, Football.